Crafting user experiences in the metaverse: A design science study - Yogesh Dwivedi (Technological Forecasting and Social Change, 2024)
Metaverse(s) is often referred to as a phenomenon where multiple and interconnected immersive experiences exist in parallel. It is an emerging trend and has drawn keen attention from consumers, practitioners, and scholars in various disciplines. Metaverses are likely to generate new business opportunities for firms and enable the firms to develop unique consumer experiences. However, the current stream of literature needs to focus on articulating how these user experiences can be designed. By adopting a design science research methodology, this study examines the user experiences that can be rendered in the metaverses. The study is conducted in two phases. In the first phase, based on expert interviews, we identify four distinct forms of user experiences and the vital techno-functional blocks required to realize these experiences. In the second phase, we utilize the best-worst method to evaluate the significance of each technological block in creating different metaverse-enabled experiences. This study enhances the metaverse literature by introducing a pentagonal techno-functional framework and categorizing the metaverse-enabled user experiences across the dimensions of create-ability and transact-ability.